2021
DOI: 10.1016/j.celrep.2021.109509
|View full text |Cite
|
Sign up to set email alerts
|

3D neuronal mitochondrial morphology in axons, dendrites, and somata of the aging mouse hippocampus

Abstract: SUMMARY The brain’s ability to process complex information relies on the constant supply of energy through aerobic respiration by mitochondria. Neurons contain three anatomically distinct compartments—the soma, dendrites, and projecting axons—which have different energetic and biochemical requirements, as well as different mitochondrial morphologies in cultured systems. In this study, we apply quantitative three-dimensional electron microscopy to map mitochondrial network morphology and complexity i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 50 publications
5
75
0
1
Order By: Relevance
“…While most ssTEM techniques require skill and are labor-intensive, FIB-SEM, SBF-SEM, and ATUM-SEM are automatized and provide high-resolution 3D images [ 16 , 52 , 53 , 54 ] dramatically improving the interpretation of the morphology of tissue and cell samples. Amira software and other similar software ( Supplementary Table S7 ) can be used for FIB-SEM, SBF-SEM, and ATUM-SEM images [ 23 , 56 , 57 , 58 ]. For studies with large samples, SBF-SEM is faster and offers larger fields of view than FIB-SEM [ 54 ]: thus, we combined SBF-SEM with the versatility, ease of use, and features of the Amira software for analysis of the SBF-SEM images.…”
Section: Discussionmentioning
confidence: 99%
“…While most ssTEM techniques require skill and are labor-intensive, FIB-SEM, SBF-SEM, and ATUM-SEM are automatized and provide high-resolution 3D images [ 16 , 52 , 53 , 54 ] dramatically improving the interpretation of the morphology of tissue and cell samples. Amira software and other similar software ( Supplementary Table S7 ) can be used for FIB-SEM, SBF-SEM, and ATUM-SEM images [ 23 , 56 , 57 , 58 ]. For studies with large samples, SBF-SEM is faster and offers larger fields of view than FIB-SEM [ 54 ]: thus, we combined SBF-SEM with the versatility, ease of use, and features of the Amira software for analysis of the SBF-SEM images.…”
Section: Discussionmentioning
confidence: 99%
“…The results herein revealed that the reduction of mitochondrial respiratory complex activity in the aged hippocampus was inconsistent with a previous report [ 21 ]. Recent 3D electron microscopic study demonstrated that mitochondrial morphology in different compartments of CA-1 and dentate gyrus neurons changed with aging [ 22 ]. Stimulating mitochondrial genesis and enhancing complex activity have been thought as efficient ways of developing antiaging medicine.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity makes the gastrocnemius ideal to study changes in mitochondrial dynamics. Other studies on the effects of aging on mitochondria in human and mouse skeletal muscle have focused on mitochondrial mutations 18 . Our 3D reconstruction of aged skeletal gastrocnemius muscle is a novel approach to study the connections between mitochondria and to determine how disconnections and reduced mitochondrial communication impact oxidative phosphorylation.…”
Section: Introductionmentioning
confidence: 99%